Một vài phương pháp hiệu chỉnh dữ liệu bản đồ số hóa - Đức, Đặng Văn (Journal of Computer Science and Cybernetics, 2016)
This paper deals with an algorithm for the reduction of the numbers of the points to represent a digitized line and a method of processing the spetial conficts in the line generalization which are used to design an integrated software for geographical information, maps and graphics database. The methods have been used in the development work of a new software called PopMap by Vietnam IOIT for United Nations Department for Economic and Social Information and Policy Analysis (DESIPA).